Kedudukan Akta PPAT Sebagai Alat Bukti Dalam Perkara Pidana - Nathania Permata Satriawan (Jatiswara, 2017)
This research aims to examine and analyze the position of PPAT’s deed that used as evidence in criminal cases and the power of proof of PPAT’s deed which serve as evidence in criminal case. This research is a normative legal research by using the legislation approach, concept approach and case approach. The results is that the position of the deed’s of PPAT as evidence in a criminal case is the same as other evidence as a proof of letter and its unbound as regulated in Article 187 of KUHAP. The judge does not have believe that the content of the deed is true because in examining the case findtruth material, and other evidence is needed to meet the minimum evidentiary as regulated in Article 183 of KUHAP.